Effectiveness of cognitive therapy and behavior therapy treatment moddules intervention in group counseling among stress nurses - Wan Anor, Wan Sulaiman; Fatimah, Yussoff; Mohd Dahlan, A. Malek; Ahmad Rozelan, Yunus (2014)
This Study was conducted as to explore the effectiveness of the treatment modules in group counseling between the Cognitive Therapy Group Counseling and Behavior Therapy Group Counseling in reducibg stress level among nurses in Woman and Children Hospital in Kota Kinabalu. The Fact, nurses who have joined either treatment have shown some decrease in their stress level. However when comparing between the two (CTGC and BTGC), BTGC showed better results in reducing stress level among nurses in the hospital. Therefore, both CTGC and BTGC are suitable to reduce stress among nurses in the hospital.